PENILAIAN KINERJA (PERFORMANCE ASSESSMENT) PESERTA DIDIK DALAM PRAKTIKUM MATERI LARUTAN PENYANGGA (BUFFER) - HALIMATUN SA’DIAH; Lazulva lazulva; Arif Yasthophi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aimed at knowing the students' performance ability in conducting chemistry practicum using performance assessment instruments. Questionnaires and student psychomotor observation sheets on buffer solution material were used for collecting the data, the observation sheet has indicators: 1) preparing preparations before doing the practicum, 2) skills in preparing tools and materials, 3) skills in conducting experiments in accordance with the practicum guide, 4) skills in using tools and taking materials, 5) drawing skills or recording the results of practical observations, 6) ability in creating, taking initiative. This research was conducted at Vocational High Schools of Ikasari Pharmacy and Abdurab Pekanbaru. This research used a qualitative descriptive. The population in this research were students at Vocational High Schools of Ikasari Pharmacy and Abdurab Pekanbaru with samples 61 students that were selected using a purposive sampling technique. The assessment results of the performance indicators in preparing preparations before conducting the practicum was 95.49%, skills in preparing tools and materials were 85.04%, skills in conducting experiments in accordance with the practicum guide was 88.66%, skills in using tools and taking materials were 93.03%, skills in drawing or recording the results of practical observations was 88.93% and the ability in creating, taking initiative were 88.17%, Overall the mean scores of the results students’ performance assessment in practicum the buffer solution material were 89.88%. Based on these results, it could be concluded that the student performance assessment observation sheet was in very good category in measuring students' psychomotor abilities on the main topic of buffer solutions. Keywords: Performance Assessment Instrument, Psychomotor Ability, Buffer Solution